Teacher’s Strategies to Protect Misbehavior of Students - Sumani Sumani; Bukman Lian; Yessi Fitriani (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
This study aimed at determining the types of student delinquency and preventive, repressive and curative actions in dealing with delinquency in SD Negeri 6 Pulau Rimau, Banyuasin. The data source of this study from 6 people, principal, 3 teachers and 2 student organizations. The method used descriptive qualitative and applied observation, documentation and interviews. The results showed that 1) the teacher's strategy in solving students' misbehavior is through struggles and countermeasures such as making school rules and penalties for students who do misbehavior; 2) the preventive action taken by the teacher is to always advise and remind the students of delinquency in school in advance. After that the teacher tries to motivate students not to do mischief again; 3) repressive actions taken by the teacher are by conducting guidance and direction as well as punishment with the aim of being able to discourage students; 4) curative action taken by both the teacher and the school as a healing attempt is to provide severe penalties to cooperate with the guardian's parents by calling to come to schoo; 5) the forms of juvenile delinquency in SD Negeri 6 Pulau Rimau were saying rude and dirty sentences, scribbling on school walls with inappropriate writing, not doing assignments, not keeping the school clean, conflicting with friends and damaging facilities school.